Application of Resources Based View on Computer Assisted Audit Techniques - Handoko, Bambang Leo; Lindawati, Ang Swat Lin; Mustapha, Mazlina (International Journal of Psychosocial Rehabilitation, 2020)
Resource Based View (RBV) can be said as an approach to achieving competitive advantage which argues that organizations must look inside the company to find sources of competitive advantage rather than seeing a competitive environment for it. Public accounting firm as a place of financial auditors or external auditors also compete with one another. Big 4, big 10 and other public accounting firms compete with each other over clients. A public accounting firm can increase its competitive advantage by using resources based view. The application of resource-based view in this case is with public accounting firms adopting computer assisted audit techniques. Computer assisted audit technique is suspected to improve the performance, efficiency and effectiveness of the auditor. Our research is a qualitative research. We use a literature study approach, complete with primary data collection through interviews and observations. The results of our study say that computer assisted audit techniques improve auditor performance through: data extraction, data analysis, inspection of electronic data processing systems, help make audit reports